188k views
10 votes
20 points

Determine whether the statement is true or false. If the statement is​ false, make the necessary​ change(s) to produce a true statement.


To solve the system below by substitution, replace y in the second equation with 7−6x.


6x−y=7


2x+y=5


This statement is true.


This statement is false. To solve the system by​ substitution, replace x in the second equation with 7−6x.


This statement is false. To solve the system by​ substitution, replace y in the first equation with 7−6x.


This statement is false. To solve the system by​ substitution, replace y in the second equation with 6x−7.

2 Answers

11 votes

Answer: This statement is false. To solve the system by​ substitution, replace y in the second equation with 6x−7.

User Tobias Theel
by
5.5k points
11 votes

Answer:

To solve the system below by substitution, replace y in the second equation with 7−6x.

==> False

This statement is false. To solve the system by substitution, replace x in the second equation with 7−6x.

==> False.

This statement is false. To solve the system by substitution, replace y in the first equation with 7−6x.

==> False

This statement is false. To solve the system by substitution, replace y in the second equation with 6x−7.

==> True.

From the first equation, 6x-y=7

y= 6x-7

User Skynetch
by
5.5k points